Pulsed laser deposition of porous N-carbon supported cobalt (oxide) thin films for highly efficient oxygen evolution. Issue 80 (16th September 2016) - Bayatsarmadi, Bita; Zheng, Yao; Casari, Carlo Spartaco; Russo, Valeria; Qiao, Shi-Zhang
Abstract : A robust porous N-carbon supported cobalt (oxide) film has been developed by pulsed laser deposition as a highly efficient OER electrode. Abstract : Identification of efficient non-precious metal catalysts for the oxygen evolution reaction (OER) remains a great challenge. Here we report robust cobalt (oxide) nanoparticles deposited on a porous nitrogen-doped carbon (N-carbon) film prepared by pulsed laser deposition under a reactive background gas, which exhibit highly efficient OER performance with a low overpotential and high stability.